The honours learning environment of Windesheim University of Applied Sciences - Tineke Kingma; Karien Dommerholt; Liesbeth Rijsdijk (Hanze UAS, 2017)
This paper presents the application of theories and experiences in the day-to-day environment of honours education in a so-called honours learning environment. In 2009, Windesheim University of Applied Sciences (UAS) started with honours education. An important question from the start was: what characterizes the honours learning environment? Based on experience, knowledge exchange and input from theory, the honours learning environment was developed, which is the fundament of honours and talent development at Windesheim UAS. The eight characteristics are illustrated by animations and explanations based on scientific studies.